Destannylative pummerer-type rearrangement of 1-(phenylsulfinyl)-1-(tributylstannyl)cyclopropane - Manat Pohmakotr (2018)
1-(Phenylsulfinyl)-1-(tributylstannyl)cyclopropane on treatment with acyl chlorides or alkyl chloroformate in refluxing dichloromethane afforded 1-acyloxy-1-phenylsulfenyl- and 1-alkoxycarbonyloxy-1-phenylsulfenylcyclopropanes, respectively. The reaction involves the Pummerer-type rearrangement with loss of tributylstannyl group. © 1989.